Harmfulness of insects of the Sievers apple tree (Malus sieversii) in Kazakhstan - GULZHANAT TANABEKOVA; ASHAT TURSYNKULOV; ROMAN JASHENKO; LU ZHAOZHI (Society for Indonesian Biodiversity, 2024)
Abstract. Tanabekova G, Tursynkulov A, Jashenko R, Zhaozhi L. 2024. Harmfulness of insects of the Sievers apple tree (Malus sieversii) in Kazakhstan. Biodiversitas 25: 3168-3178. The purpose of this study was to assess the degree of harmfulness of insects commonly found in Sievers apple trees (Malus sieversii (Ledeb.) M.Roem.) and to identify entomopathogenic nematodes in soil samples from apple orchards. In this regard, the insect pests of the Sievers apple tree are divided into six main complexes according to the degree of harmfulness of insects. The food specialization and feeding relationships of insects are extremely important in plant protection. In many cases, the development of pest control measures is impossible without an accurate accounting of their host plants and various pest populations. During the research, the Iley Alatau and Zhetysu Alatau were compared in terms of the occurrence of species and the number of species damaging the Sievers apple tree. According to our data, there are more than a hundred insects on the Sievers apple tree in these areas, of which only a few species are of operational importance: Cyd?a (Laspeyres?a) pomonella L?nnaeus, 1758; Arch?ps rosana Linnaeus, 1758; Archips crataegana Hübner, 1799; Yponomeuta mal?nellus Zeller, 1838; Yponomeuta padellus L?nnaeus, 1758; Graphol?ta molesta Busck, 1916; Aph?s pom? De Geer, 1773; Lep?dosaphes ulm? L?nnaeus, 1758; Haplothr?ps reuter? ?arny, 1907; Dasyneura mal? K?effer, 1904; St?gmella malella Sta?nton, 1854. Their damage is episodic and is confined to the periods of mass reproduction of these species. Additionally, soil samples from apple orchards in the foothill zone were analyzed for the presence of entomopathogenic nematodes. The study revealed the presence of nematodes of the genus Steinernema, suggesting potential for developing biological control strategies against insect pests in Sievers apple orchards.